2023
DOI: 10.1021/acsaenm.3c00490
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic Cu2O-CuO/Cu Mesh Catalyst for Ambient Ozone Removal

Jian Guan,
Yacong Guo,
Guojun Ma
et al.

Abstract: Nowadays, it is highly desired to decompose near-ground O3, as it is not only harmful to humans but also can react with other gases to form secondary pollutants because of its strong oxidizing properties. Here, a monolithic Cu2O-CuO/Cu mesh catalyst is fabricated by a facile thermal oxidation and reduction (at 350 °C) method using Cu mesh. The as-synthesized catalyst can maintain 98% conversion for 5 h to 0.34 ppm of O3, at space velocity of 23,000 h‑1 and RH 45% which is one of the highest in the literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
(74 reference statements)
1
0
0
Order By: Relevance
“…The whole XPS spectrum of Cu 2 O@rGO possessed Cu, O, and C electronic orbitals, which were basically consistent with those of pure Cu 2 O. Furthermore, the Cu 2 O spectrum showed that the strong characteristic peaks symbolizing Cu + 2p 3/2 and Cu + 2p 1/2 were located at 932.38 and 952.38 eV, whereas the characteristic peaks symbolizing Cu ion 2p 3/2 and Cu ion 2p 1/2 were located at 934.68 and 955.08 eV, respectively [39]. As a comparison, both peak positions symbolizing Cu + in Cu 2 O@rGO redshifted, which indicates that there is an interaction between rGO and Cu 2 O [40].…”
Section: Microstructure Of the Synthesized Nanoparticlessupporting
confidence: 74%
“…The whole XPS spectrum of Cu 2 O@rGO possessed Cu, O, and C electronic orbitals, which were basically consistent with those of pure Cu 2 O. Furthermore, the Cu 2 O spectrum showed that the strong characteristic peaks symbolizing Cu + 2p 3/2 and Cu + 2p 1/2 were located at 932.38 and 952.38 eV, whereas the characteristic peaks symbolizing Cu ion 2p 3/2 and Cu ion 2p 1/2 were located at 934.68 and 955.08 eV, respectively [39]. As a comparison, both peak positions symbolizing Cu + in Cu 2 O@rGO redshifted, which indicates that there is an interaction between rGO and Cu 2 O [40].…”
Section: Microstructure Of the Synthesized Nanoparticlessupporting
confidence: 74%
“…Pure CuO nanowires have poor catalytic activity for ozone decomposition reactions, but after constructing Cu 2 O nanocones, this Cu composite structure exhibits high activity, making it suitable as a practical catalyst (Figure 8b). Guan et al [65] further modified the copper mesh and constructed Cu 2 O nanocones on the surface, then applied it to the nonwoven cloth (Figure 8c). The cost of modified copper mesh is lower than that of foam metal, which helps to remove ozone in daily applications, expanding the application of ozone decomposition catalysts from fixed (indoor or enclosed spaces) to mobile scenarios.…”
Section: The Monolithic Copper-based Catalystmentioning
confidence: 99%
“…In contrast, the use of copper foam requires loading in the tubular catalytic device to form an integrated catalyst, whether it is a wet redox process or a gas-phase redox process [66] (Figure 8d). [64], Royal Society of Chemistry, copyright 2020 [65], and American Chemical Society, copyright 2023 [66]).…”
Section: The Monolithic Copper-based Catalystmentioning
confidence: 99%
See 1 more Smart Citation